Género y lugar de procedencia: dos variables clave en la integración escolar del alumnado extranjero - Goenechea Permisán, Cristina (Revista Complutense de Educación, 2005)
Given the fact that an increasing number of immigrant students are being educated in Spanish state schools, there is an urgent need to examine the situation of such students. It is therefore necessary to highlight the difficulties faced by these students, with a view to identifying ways to solve and also prevent such problems. Throughout this paper, the focus is on the educational situation of immigrant students in Galicia. Specifically, we analyse the difficulties faced by these students, depending on two important variables: gender and country of origin.
Keywords: Intercultural Education; immigrant students; gender; Galicia; Spain